Konstruksi Nilai-Nilai dalam Peristiwa Fathu Makkah - Abdur Rouf Hasbullah (Universitas Islam Tribakti Lirboyo Kediri, 2022)
Fathu Makkah is the conquest carried out by the Prophet Muhammad Saw in the 8th year H, where history records a conquest of the city without shedding any blood. The purpose of this research is to describe the values that are built in the events of Fath Al-Makkah. then this research was conducted using a qualitative approach that describes the results of research in accordance with its objectives and with analysis or often called the descriptive analysis method. This research found that Fathu Makkah was not only an event of the conquest of the city. But from this event, this research found several meanings that could be noble values that can be realized in everyday life. There are about 4 values contained in the story including: The value of openness, peace, forgiveness, and tawadhu. All of them make Fathu Makkah an important event in the history of Muslims and all mankind in general, that even in war conditions, we must prioritize human values as fellow creatures of God.